2019
DOI: 10.1002/eji.201847810
|View full text |Cite
|
Sign up to set email alerts
|

All the small things: How virus‐like particles and liposomes modulate allergic immune responses

Abstract: Recent years have seen a dramatic increase in the range of applications of virus‐like nanoparticle (VNP)‐ and liposome‐based antigen delivery systems for the treatment of allergies. These platforms rely on a growing number of inert virus‐backbones or distinct lipid formulations and intend to engage the host's innate and/or adaptive immune system by virtue of their co‐delivered immunogens. Due to their particulate nature, VNP and liposomal preparations are also capable of breaking tolerance against endogenous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 168 publications
(235 reference statements)
0
14
0
Order By: Relevance
“…In this approach, allergen‐encoding cDNA is fused to virus‐encoding DNA (Matrix protein, p15MA) 151 or to a glycosyl‐phosphatidyl inositol anchor acceptor sequence 152 to be expressed either inside or outside of VNPs, respectively. Encasement of full‐length allergens within VNPs should ensure that such VNP preparations are nonanaphylactogenic when applied to already sensitized individuals 153 . In a preclinical model of mugwort pollen allergy 154 such particles were successfully used for prophylactic vaccination 155 .…”
Section: Molecular Immunotherapy For Future Treatment and Allergen‐spmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, allergen‐encoding cDNA is fused to virus‐encoding DNA (Matrix protein, p15MA) 151 or to a glycosyl‐phosphatidyl inositol anchor acceptor sequence 152 to be expressed either inside or outside of VNPs, respectively. Encasement of full‐length allergens within VNPs should ensure that such VNP preparations are nonanaphylactogenic when applied to already sensitized individuals 153 . In a preclinical model of mugwort pollen allergy 154 such particles were successfully used for prophylactic vaccination 155 .…”
Section: Molecular Immunotherapy For Future Treatment and Allergen‐spmentioning
confidence: 99%
“…Encasement of full-length allergens within VNPs should ensure that such VNP preparations are nonanaphylactogenic when applied to already sensitized individuals. 153 In a preclinical model of mugwort pollen allergy 154 such particles were successfully used for prophylactic vaccination. 155 However, there is so far no experience with virus-like particles in clinical AIT studies in patients, although one study performed in nonallergic subjects showed the induction of allergen-specific IgG antibodies.…”
Section: Virus-like Particle-coupled Allergensmentioning
confidence: 99%
“…Recently, an alternative approach for engineering virus-like nanoparticles (VNP) was reported. In the VNPs, allergen-encoding cDNA is fused to virus-encoding DNA (Matrix protein, p15MA) ( 62 ) or to a glycosyl-phosphatidyl inositol anchor acceptor sequence ( 63 ) to be expressed either inside or outside of VNPs, respectively ( 64 ). In a mouse model of mugwort pollen allergy ( 65 ) such particles were successfully used for prophylactic vaccination ( 66 ) but so far there is no experience with VNPs in clinical AIT studies in patients and this approach therefore needs to be further developed.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been investigations into how VLPs can be used as NPs for targeted delivery of drugs, [ 44 ] gene therapy, [ 47 ] and the treatment of noninfectious diseases such as cancer, [ 43,45,48 ] neurodegenerative diseases, [ 49,50 ] hypertension, [ 51–53 ] nicotine addiction, [ 54 ] diabetes, [ 55 ] and even allergies. [ 50,56 ]…”
Section: Nanobiomedical Approaches To Covid‐19 Vaccinesmentioning
confidence: 99%
“…There have also been investigations into how VLPs can be used as NPs for targeted delivery of drugs, [44] gene therapy, [47] and the treatment of noninfectious diseases such as cancer, [43,45,48] neurodegenerative diseases, [49,50] hypertension, [51][52][53] nicotine addiction, [54] diabetes, [55] and even allergies. [50,56] VLPs are relatively inexpensive to produce, but the production process itself is complicated. [47] VLPs self-assemble and can range from a simple single-layered VLP to a complex multilayered VLP composed of multiple proteins or decorated with various glycoproteins, depending on the parent virus and the purpose of the VLP.…”
Section: Virus-like Particles For Infectious Diseasesmentioning
confidence: 99%